2017
DOI: 10.1038/hortres.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

The WRKY transcription factor HpWRKY44 regulates CytP450-like1 expression in red pitaya fruit (Hylocereus polyrhizus)

Abstract: Red pitaya (Hylocereus polyrhizus) fruit is a high-value, functional food, containing a high level of betalains. Several genes potentially related to betalain biosynthesis, such as cytochrome P450-like (CytP450-like), have been identified in pitaya fruit, while their transcriptional regulation remains unclear. In this work, the potential involvement of a WRKY transcription factor, HpWRKY44, in regulating CytP450-like1 expression in pitaya fruit was examined. HpWRKY44, a member of the Group 1 WRKY family, conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 43 publications
(74 reference statements)
2
70
0
Order By: Relevance
“…At least one of these bHLH genes, ORF11 , is highly expressed in betacyanic tissue in S. oleracea , consistent with a role in betalain pigmentation (Cai et al ., ). Finally, a recent study has shown that a WRKY transcription factor, HpWRKY , identified by a RNAseq screen in the Hylocereus polyrhizus , can bind a W‐box motif present in the promoter of a CYP76AD1 homologue from the same species (Cheng et al ., ). WRKY transcription factors have more recently emerged as putative interacting partners with MBW complexes, controlling anthocyanin synthesis in both A. thaliana and Petunia hybrida (reviewed in Lloyd et al ., ).…”
Section: Transcriptional Regulation Of the Betalain Pathway (Bvmyb1)mentioning
confidence: 97%
“…At least one of these bHLH genes, ORF11 , is highly expressed in betacyanic tissue in S. oleracea , consistent with a role in betalain pigmentation (Cai et al ., ). Finally, a recent study has shown that a WRKY transcription factor, HpWRKY , identified by a RNAseq screen in the Hylocereus polyrhizus , can bind a W‐box motif present in the promoter of a CYP76AD1 homologue from the same species (Cheng et al ., ). WRKY transcription factors have more recently emerged as putative interacting partners with MBW complexes, controlling anthocyanin synthesis in both A. thaliana and Petunia hybrida (reviewed in Lloyd et al ., ).…”
Section: Transcriptional Regulation Of the Betalain Pathway (Bvmyb1)mentioning
confidence: 97%
“…TFs such as the well-known WRKY ( 19 , 20 ) and basic leucine zipper (bZIP) ( 21 , 22 ) are proteins that control the transcription of a series of genes, thus are popular genes in both basic biology and applied breeding programs ( 23–26 ). The defining feature of TFs is that they contain at least one conserved DNA-binding domain that could bind to a specific corresponding DNA sequence, usually in the promoter region.…”
Section: Resultsmentioning
confidence: 99%
“…Pitaya is named green dragon fruit 1 or red dragon fruit 2 . Originated in the tropics of Central America, 3 Taiwan Province of China began to introduce pitaya in early 1990s, 4 and in recent years, pitaya has been introduced to other provinces including Guangxi, Guangdong, Fujian, Yunnan, Hainan, and Guizhou 5 . The whole area of pitaya in China has an area of about 35–40 thousand hectares 6–8 .…”
Section: Introductionmentioning
confidence: 99%